Revised distribution and phytosociological data of Orobanche coerulescens Stephan in Willd. (Orobanchaceae): Poland in relation to Central Europe - Piwowarczyk, Renata (Biodiversity: Research and Conservation, 2012)
Orobanche coerulescens has a Eurasian distribution. The species is classified as extinct at most of its localities at the western limit of its range. Its populations are very scarce and critically endangered in Central Europe. This work presents the current distribution of O.coerulescens in Poland, based on a critical revision of herbarium and literature data as well as results of original field research, and reviews its distribution in Central Europe (partly in Eastern Europe). Habitats, plant communities, and migration routes of O.coerulescens in Central Europe are discussed. The species was initially known in Poland from now historical localities in Pomerania and the valley of the lower Vistula. In 2000-2011 it was recorded at 9 localities in Podlasie, the Małopolska Upland (Wyżyna Małopolska), and the Łódź Hills (Wzniesienia Łódzkie). Its abundance at the localities ranged from a few to over 1000 shoots. These are the largest populations of O.coerulescens at its western and north-western range limits.